Policy Innovation in Stunting Reduction: A Case Study of Lamandau Regional Government Strategy - Ismy Khairiyah; M. Yusuf; M. Riban Satia (Univiversitas Dr. Djar Wattiheluw, 2025)
Stunting constitutes a significant public health concern with long-term implications for children's growth and development. This study investigates policy innovations implemented by the regional government of Lamandau Regency to address stunting. Utilizing a qualitative approach, data were collected through interviews, observations, and document analysis. The findings indicate that innovative strategies include the integration of health services, education, and community empowerment. Programs such as nutrition awareness campaigns, health cadre training, and the enhancement of child health monitoring systems have played a crucial role in reducing stunting rates in the region. However, challenges persist, particularly in ensuring access to health services in remote areas. This study underscores the necessity of more inclusive and sustainable policies to enhance the effectiveness of stunting reduction initiatives. Consequently, the findings provide a valuable reference for other regions in developing and implementing similar policy interventions.